Redistribution and the monetary-fiscal policy mix - Saroj Bhattarai; Jae-Won Lee; Choongryul Yang (Quantitative Economics, 2023)
We show that the effectiveness of redistribution policy is tied to how much inflation it generates, and thereby to monetary-fiscal adjustments that ultimately finance the transfers. In the monetary regime, taxes increase to finance transfers while in the fiscal regime, inflation rises, imposing inflation taxes on public debt holders. We show analytically that the fiscal regime generates larger and more persistent inflation than the monetary regime. In a two-sector model, we quantify the effects of the CARES Act in a COVID recession. We find that transfer multipliers are larger, and that moreover, redistribution is Pareto improving, under the fiscal regime.
Keywords: E53; E62; E63; 330; Household heterogeneity; redistribution; monetary-fiscal policy mix; transfer multiplier; welfare evaluation; COVID-19; CARES Act